Puntos cuánticos: nueva aportación de la nanotecnología en investigación y medicina - Pombo Barros, V.; Goyanes Villaescusa , V. (Revista Complutense de Ciencias Veterinarias, 2011)
Quantum Dots (QDs) are more fotostable, monochromatic and brilliant than any standard fluorocrome. These qualities and their capacity to build different constructors (targeted with antibodies, oligonucleotides, Biotine, lectines, magnetic ions, etc) allow them a wide versatility and sensibility, even to single molecular levels. Furthermore, improving standard PSA and other tests QDs represent a new alternative in Western blotting and flow citometry. Laboratories-on-a-chip, one of the more original nanoproducts, makes possible a wide variety of clinical tests simultaneously at real time, low cost and a minimal amount of sample. QDs are also being employed in biotechnology to genetic identifications through multicolour barcodes on microchips. QDs nanocrystal–labeled antibodies allow simultaneous and safe detection of multiple molecules in metabolic tracts inside living cells. Even traffic, localization, turnover and function of proteins can be understood at a time, giving birth to Visual Proteomics. New implementations in clinical oncology enable cancer cells recognition in circulating blood, more precise identification of the sentinel node in breast neoplasia as well as selectively delimitate malignant growths in brain surgery. Are we close to a sequential diagnosis and therapy in a single medical act by Quantum Dots; the optical biopsy? Regenerative medicine promises replacement therapy of organs and tissues growth “in vitro”. Carbon Nanotubes improve the substratum to steam cells differentiation as well as under control drugs release, particularly targeted citostatics or genetic vectors. Nanotechnology and particularly Quantum Dots represent the future tools for laboratory diagnosis, cell biology and cancer therapy.